2014
DOI: 10.1007/s00449-014-1277-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel glutaminase free l-asparaginase from Nocardiopsis alba NIOT-VKMA08: production, optimization, functional and molecular characterization

Abstract: Studies were carried out for the optimization and production of novel extracellular glutaminase-free L-asparaginase from Nocardiopsis alba NIOT-VKMA08. Among the tested carbon and nitrogen sources, maximum L-asparaginase production was observed with a combination of L-asparagine and maltose (1.5%) and twofold increase in yield (18.47 IU mL(-1)) was observed with newly optimized NIOT-asparaginase medium. Activity of the purified enzyme was moderately inhibited by various divalent cations and thiol group blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 34 publications
0
12
0
4
Order By: Relevance
“…(Moorthy et al, 2010), Pseudomonas aeruginosa (Abdel-Fattah and Olama, 2002), Enterobacter aerogenes (Mukherjee et al, 2002), Zymomonas mobilis (Pinheiro et al, 2001), Bacillus licheniformis (Sudhir et al, 2014), Nocardiopsis alba NIOT-VKMA08 (Meena et al, 2015), Bacillus subtilis B11−06 (Jia et al, 2013), and Staphylococcus sp. OJ82 (Sangwon et al, 2014) have been found to produce L-asparaginase.…”
Section: Introductionmentioning
confidence: 98%
“…(Moorthy et al, 2010), Pseudomonas aeruginosa (Abdel-Fattah and Olama, 2002), Enterobacter aerogenes (Mukherjee et al, 2002), Zymomonas mobilis (Pinheiro et al, 2001), Bacillus licheniformis (Sudhir et al, 2014), Nocardiopsis alba NIOT-VKMA08 (Meena et al, 2015), Bacillus subtilis B11−06 (Jia et al, 2013), and Staphylococcus sp. OJ82 (Sangwon et al, 2014) have been found to produce L-asparaginase.…”
Section: Introductionmentioning
confidence: 98%
“…Different carbon sources have different effects on L-asparaginase production from Streptomyces. S. longsporusflavus and S. albidoflavus produced the maximum amount of Lasparaginase when grown on soluble starch [13,23] whereas S. phaeochromogenes and S. tendae produced the maximum activity on glycerol and sucrose, respectively [24]. However, few studies used lactose for Actinobacterial Lasparaginase production.…”
Section: Discussionmentioning
confidence: 99%
“…Os sintomas das reações alérgicas à L-asparaginase incluem febre, dor, urticária, exantema, anafilaxia e desconforto respiratório, sendo que a maioria dos pacientes (84%) desenvolve reações alérgicas grau 2, enquanto que 15% destes desenvolvem grau 3, e apenas 0,5% grau 4 (CHEN et al, 2010 (CHAN et al, 2014;MEENA et al, 2015;MEHTA et al 2014;SUDHIR et al, 2014;VERMA et al, 2014;OFFMAN et al, 2011;RAMYA et al, 2011;REINERT et al 2006).…”
Section: Hipersensibilidade E Formação De Anticorpos Anti-l-asparaginaseunclassified
“…Dentre os estudos citados, Meena et al (2015), Sudhir et al (2014), Ramya et al (2011) (MEENA et al, 2015;SUDHIR et al, 2014;RAMYA et al, 2011;REINERT et al 2006). Já os pesquisadores Chain et.…”
Section: Hipersensibilidade E Formação De Anticorpos Anti-l-asparaginaseunclassified
See 1 more Smart Citation